A simple tool for forecasting the mechanical response of anchored wire mesh panels. Issue 1 (August 2021) - Pol, Antonio; Gabrieli, Fabio; Bost, Marion
Abstract: Anchored wire meshes are applied worldwide as protective structures against rockfall. The mechanical performance of a wire mesh is evaluated through laboratory tests, but these are generally not representative of the field conditions. This paper presents a simple tool to predict the force-displacement response of an anchored mesh panel to an out-of-plane load, extending the experimental standard punch test characteristic values (ISO 17745, ISO 17746, UNI 11437) to field conditions. Discrete element simulations are used to provide analytical relations that account for the effect of the different problem's variables on the ultimate resistance and maximum deflection of a mesh panel. The numerical results are subsequently used to define a master curve permitting the force-displacement response of a generic anchored mesh panel to be forecasted. Finally, the master curve is validated against ex-post simulations, and practical implications are discussed.